Evaluation of pH-sensitive polyurethane 2-diethylaminoethyl methacrylate hybrids potentially useful for drug delivery developments - Pardini, Francisco (2015)
Smart sensitive polymers have been used to improve processes in drug delivery. In this article, we evaluate the behavior of polyurethane/N,N-diethylaminoethyl methacrylate hybrids (PU/DEA) as pH- responsive polymers potentially useful for drug delivery systems development, using Rhodamine 6G (Rh6G) as a model drug. A detailed pH responsive characterization was performed by swelling studies and scanning electron microscopy (SEM). Two drug loading methods on drug release-immersion and direct loading were evaluated. The interaction between Rh6G and the polymer matrix was studied by Fourier Transform Infrared (FTIR) spectroscopy and contact angle determination. The kinetic study of Rh6G release was performed at basic and acidic pH; the mechanism of drug delivery was analyzed using Ritger-Peppas' equation. We discuss about polymer's active sites and drug's distribution through the matrix in relation to both loading methods. Results showed a pH-responsive behavior and morphological changes when pH solution varied from 9.0 to 4.0. In the immersion loading method, results indicated a higher Rh6G molecule concentration at the surface as well as ionic interaction between the drug and polymer's carboxylic groups. Release studies confirmed the pH-sensitive hybrid systems' behavior and kinetic exponent values indicated different mechanism's transport types depending on loading method and polymer composition.